Affect Balance and Relationship With Well-Being in Nursing Home Residents With Dementia - Kolanowski, Ann M. (SAGE Publications, 2014)
The purpose of this exploratory study was to determine whether the balance of positive to negative affect can discriminate states of well-being in nursing home residents with dementia and whether affect balance is associated with activity engagement. Baseline data from a randomized clinical trial were used in this secondary analysis. Participants were 128 residents recruited from 9 nursing homes located in Pennsylvania. Participants were primarily female, Caucasian, and had a mean age of 86 years. Measures of agitation and affect were taken from video recordings of 10 observational sessions. Measures of engagement and self-reported mood were taken in real time. Ten percent of participants were categorized as having high well-being. These participants had a mean ratio of positive–negative affect of 2.21 (±0.50), a ratio significantly different than that of participants with moderate or low well-being. Affect balance was related to greater engagement in activity (r = .23; P = .008).